ANALISIS KEPUASAN MAHASISWA TERHADAP KUALITAS PEMBELAJARAN DOSEN PROGRAM STUDI PENDIDIKAN EKONOMI FKIP UNIVERSITAS RIAU - Suarman '; Sumarno '; Arum ' (PEKBIS, 2012)
This study aims to determine the level of student satisfaction in teaching andlearning in Teacher Training and Education Economics Education Studies ProgramUniversity of Riau. In addition to knowing which variables to give satisfaction to thestudent and the strategic implications of research results in order to increase studentsatisfaction in the future? In this study the respondents are 90 students forEconomic Education based quotas layered random method from each stratum /force taken the same amount as the sample that is force 2007.2008, and 2009.While the determination of the respondents use the lottery (random). Methods ofdata collection in this study using questionnaire and analytical techniques used toprocess the data is the technique of importance-performance analysis (Importance-Performance Analysis).The results showed that the level of student satisfaction FKIPEconomics Education Studies Program University of Riau as a whole includingclassification quite satisfied. This is reflected by the analysis match between thelevel of implementation of learning by the faculty with the level of student interestyield of 68.88%. Of 35 variables analyzed then there are 12 (twelve) variables thathave not been giving satisfaction and 18 (eighteen) variable is already showingsatisfaction. Strategic implications of research results to improve student satisfactionis to give priority to the variables that according to the student to have such highinterest rates, the schedule of consultations provided by the Economics EducationStudies Program faculty, lecturers return answer sheets UTS values and UAS,lecturer announces exam results timely, and professors pay attention to theprogress of students, lecturers understand the learning difficulties faced by students,and faculty foster student interest and enthusiasm in learning. Variables that havegiven such satisfaction, a lecturer at the first lecture describes the topics that matterwill be studied for one semester, a lecturer at the first lecture describes the contractteruberkaitan lecture about lecturing system, materials, perunjukan or reference,rules and forms of job evaluation systems, lecturers over matter courses, lecturersare able to explain properly, the assessment standards provided by the lecturers,lecturers use the media / learning aids that fit and attractive (sepert OHP, using theLCD, film, or images, etc.), and lecturer use language and how to communicate aclear, attractive, easily understood, and good and right.